Wine & food : pick the right wine every time - Parkinson, Jane (London, United Kingdom : Ryland Peters & Small, 2014)
"Jane Parkinson offers an up-to-date look at the global wine scene with detailed information on grape varieties and the range of wine style they contribute to. You'll learn everything you need to ever wanted or needed to know about red, white, rosé, fizz, fortified and dessert wines, and how best to enjoy them. Insider knowledge on storing and pouring wine, and what food to serve it with, shows you exactly how to pick the right wine every time."
The bar -- The cellar -- Pick the right wine: white -- Pick the right wine: fortified, sweet & fizz -- The table.
Includes index.
Keywords: WINE AND WINE MAKING